Information Marketing Analysis at Upt. Lancang Kuning University Library - Agusniati; Valencia; Ira Melisa (Formosa Journal of Applied Sciences, 2023)
The purpose of this article is to find out how to market information at the Lancang Kuning University Library Upt. This study uses a qualitative research method with a descriptive. The research subjects used as sources in this study were librarians at the Lancang Kuning University Upt.Library, totaling one librarian. Based on the results of observation and interviews that researchers have conducted, it is known that Upt.Universitas Lancang Kuning has several services such as circulation services, references, photocopying, BI corner and digital services as well as information retrieval services through OPAC. Upt. Lancang Kuning University Library also carries out information marketing processes through digital and conventional. Based on the results of interviews that researchers have conducted, information is obtained that Upt.Library of Lancang Kuning University conducts information marketing by updating/incorporating information about the latest collections in the library into the website or OPAC.